The Role of Business Incubators in Encouraging Students to Develop Entrepreneurial Ideas - Prety Diawati; Hesti Sugesti (Indo-MathEdu Intellectuals Journal, 2023)
In the midst of increasingly fierce competition, students as the younger generation have the potential to become innovative and highly competitive entrepreneurs. However, the first step in the entrepreneurial journey, namely developing a viable business idea, is often an obstacle for many students. The purpose of this study is to examine more deeply the role of business incubators in encouraging students to develop entrepreneurial ideas. This research is a literature review that uses a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The study results show that the role of business incubators in encouraging students to develop entrepreneurial ideas is crucial. Business incubators provide a supportive environment, valuable resources, training, infrastructure, funding sources, and collaboration opportunities that all contribute to the development of creative ideas into successful businesses. Business incubators also help develop the entrepreneurial character and mentality necessary to face the challenges and uncertainties of the business world.